Synthesis and properties of ApA analogues with shortened phosphonate internucleotide linkage - Králíková, Sárka; Buděšínský, Miloš; Barvík, Ivan; Masojídková, Milena; Točík, Zdeněk; Rosenberg, Ivan (Nucleosides, nucleotides & nucleic acids, 2011)
A complete series of the 2 '-5 ' and 3 '-5 ' regioisomeric types of r(ApA) and 2 '-d(ApA) analogues with the α-hydroxy-phosphonate C3 '-O-P-CH(OH)-C4 ″ internucleotide linkage, isopolar but non-isosteric with the phosphodiester one, were synthesized and their hybridization properties with polyU studied. Due to the chirality on the 5 '-carbon atom of the modified internucleotide linkage bearing phosphorus and hydroxy moieties, each regioisomeric type of ApA dimer is split into epimeric pairs. To examine the role of the 5 '-hydroxyl of the α-hydroxy-phosphonate moiety during hybridization, the appropriate r(ApA) analogues with 3 '(2 ')-O-P-CH(2)-C4 ″ linkage lacking the 5 '-hydroxyl were synthesized. Nuclear magnetic resonance (NMR) spectroscopy study on the conformation of the modified sugar-phosphate backbone, along with the hybridization measurements, revealed remarkable differences in the stability of complexes with polyU, depending on the 5 '-carbon atom configuration. Potential usefulness of the α-hydroxy-phosphonate linkage in modified oligoribonucleotides is discussed.
Keywords: Organophosphonates; Magnetic Resonance Spectroscopy; Poly U; Chemistry Techniques, Synthetic; magnetická rezonanční spektroskopie; techniky syntetické chemie; molekulární modely; molekulární konformace; Molecular Conformation; Models, Molecular; organofosfonáty; poly U